Lithium-rich manganese-based positive electrode material and preparation method thereof, and lithium-ion battery
By forming a nanoscale dynamic interface of cobalt and lithium in a lithium-rich manganese-based positive electrode material and introducing phosphorus and sulfur groups, Li-PS4 and Co-PS4 composites are formed, which solves the problem of structural instability and insufficient conductivity of the material at high voltage, and achieves performance improvement and cycle life extension.
Patent Information
- Application Number
- CN202411599460.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Existing lithium-rich manganese-based positive electrode materials are prone to oxygen release at high voltages, resulting in unstable structure, poor electrochemical performance, and insufficient conductivity, making it difficult to meet the needs of fast charging or high-power discharge.
By forming a nanoscale dynamic interface of cobalt and lithium in the material, the migration of cobalt and lithium ions is adjusted, the passivation after doping is avoided, and phosphorus and sulfur groups are introduced to form Li-PS4 and Co-PS4 composites, stabilizing the lattice structure and improving conductivity.
It effectively improves the structural stability, electrochemical performance and cycle life of the material, enhances the electron and ion transmission efficiency, and meets the needs of fast charging and discharging.
Smart Images

Figure CN119118213B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a lithium-rich manganese-based positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Li-rich Mn-based cathode materials have become the focus of research on lithium-ion battery cathode materials due to their high theoretical specific capacity and high energy density. However, the existing lithium-rich Mn-based materials have many technical problems in practical applications, resulting in their performance being far below expectations. These problems are mainly concentrated in the structural stability, electrochemical performance and cycle life of the materials.
[0003] Lithium-rich manganese-based materials are prone to oxygen release under high voltage. This irreversible precipitation of oxygen will not only destroy the lattice structure of the material, but also cause the battery to produce capacity decay during the cycle. Due to the high operating voltage of lithium-rich manganese-based materials, the release of oxygen will inevitably aggravate the lattice distortion of the material, thereby affecting the overall structural stability of the material.
[0004] The electronic and ionic conductivity of lithium-rich manganese-based materials is weak, which limits their charge and discharge speed under high-rate conditions and makes it difficult to meet the needs of fast charging or high-power discharge. Although traditional doping and surface coating technologies can improve the conductivity of materials to a certain extent, it is often difficult to maintain structural stability while improving rate performance. The uniformity of doping and coating still exists, resulting in limited improvement in material performance.
[0005] Therefore, it is necessary to provide a new solution to the above technical problems. Summary of the invention
[0006] The object of the present invention is to provide a lithium-rich manganese-based positive electrode material and a preparation method thereof, and a lithium-ion battery, which can improve the structural stability, electrochemical performance and cycle life of the positive electrode material.
[0007] To achieve the above purpose, the technical solution provided by the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing a lithium-rich manganese-based positive electrode material, which comprises the following steps:
[0009] S101: Mix and dissolve a manganese source, a cobalt source and a lithium source to prepare a metal salt solution;
[0010] S102: adding an organic phosphorus sulfide, a complexing agent and a dispersant to the metal salt solution, adjusting the pH of the system to 9-11, and reacting at 60-80° C. to obtain a precursor solution;
[0011] S103: adding a lithium hydroxide solution to the precursor solution to perform a precipitation reaction, and aging the precipitate at 50-80° C. for 4-8 hours;
[0012] S104: heating the aged precipitate at 150-200° C. for 30-60 min, washing, and drying;
[0013] S105: The dried precipitate is mixed with a lithium source and sintered in stages at a sintering temperature of 200 to 850° C. for a sintering time of 10 to 20 hours to obtain a lithium-rich manganese-based positive electrode material.
[0014] In one or more embodiments, the molar ratio of manganese, cobalt and lithium in the metal salt solution in step S101 is 1: (0.05-0.5): (1.1-1.3).
[0015] In one or more embodiments, the organophosphorus sulfide includes at least one of triethyl thiophosphate and diethyl dithiophosphate; and / or the chelating agent includes at least one of ethylenediaminetetraacetic acid, triethanolamine, and ammonia water; and / or the dispersant includes at least one of citric acid, polyethylene glycol, and polyvinyl pyrrolidone.
[0016] In one or more embodiments, the precursor solution in step S102 contains cobalt-lithium heterogeneous nanoparticles, and the average particle size of the cobalt-lithium heterogeneous particles is 50-150 nm.
[0017] In one or more embodiments, the molar ratio of the organic phosphorus sulfide to the cobalt in the metal salt solution in step S102 is (0.08~0.2): 1; and / or the molar ratio of manganese in the precursor solution to lithium in the lithium hydroxide solution in step S103 is 1: (1~1.2).
[0018] In one or more embodiments, the staged sintering in step S105 includes: pre-sintering at 250° C. for 2 to 4 hours; then keeping at 600° C. for 4 to 6 hours; and finally sintering at 850° C. for 10 hours.
[0019] In one or more embodiments, the lithium-rich manganese-based positive electrode material contains Li-PS4 and Co-PS4 complexes, and the Li-PS4 and Co-PS4 complexes are located on the grain surfaces and grain boundary regions of the lithium-rich manganese-based positive electrode material.
[0020] In one or more embodiments, a cobalt-oxygen cluster nanostructure is formed on the grain surface and grain boundary region of the lithium-rich manganese-based positive electrode material.
[0021] In a second aspect, the present invention provides a lithium-rich manganese-based positive electrode material, and the lithium-rich manganese-based positive electrode material is prepared by the aforementioned preparation method.
[0022] In a third aspect, the present invention provides a lithium-ion battery comprising the aforementioned lithium-rich manganese-based positive electrode material.
[0023] Compared with the prior art, the lithium-rich manganese-based positive electrode material and its preparation method, and the lithium-ion battery provided by the present invention can adjust the migration of cobalt and lithium ions under different electrochemical states by forming a nanoscale dynamic interface between cobalt and lithium inside the material, thereby avoiding the passivation phenomenon after doping in the prior art; and introduce phosphorus-sulfur groups into the material system to interact with the lithium and cobalt elements in the material to form Li-PS4 and Co-PS4 complexes, which can effectively stabilize the lattice structure of the material and improve the conductivity of the material by improving the efficiency of electron and ion transmission. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 Flow chart of a method for preparing a lithium-rich manganese-based positive electrode material in one embodiment of the present invention;
[0026] Figure 2 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention;
[0027] Figure 3 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 4 of the present invention;
[0028] Figure 4 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 of the present invention;
[0029] Figure 5 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 2 of the present invention;
[0030] Figure 6 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 3 of the present invention;
[0031] Figure 7 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 5 of the present invention;
[0032] Figure 8This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 6 of the present invention;
[0033] Fig. 9 This is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 7 of the present invention. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0035] It should be noted that, unless otherwise indicated, all numbers used in the specification and claims to represent feature sizes, quantities and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.2, 1.4, 1.55, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0036] Lithium-rich manganese-based cathode materials have become a research hotspot due to their high theoretical specific capacity and high energy density, but their practical application faces many challenges due to their unstable structure and poor electrochemical performance. In the existing technology, lithium-rich manganese-based cathode materials have many performance bottlenecks, especially the problem of oxygen release under high voltage conditions, insufficient conductivity, poor structural stability and limited cycle life.
[0037] In the process of analyzing the prior art, the inventors found that the existing lithium-rich manganese-based materials are prone to oxygen release under high voltage, which will destroy the lattice structure of the material and cause the battery capacity to decay rapidly during the charge and discharge cycle. Secondly, the electronic and ionic conductivity of the material is poor, resulting in the inability to fully realize its high energy density potential during high-rate charge and discharge. In addition, although traditional doping and surface coating technologies have improved conductivity and stability to a certain extent, due to the problem of doping uniformity, the performance improvement of the material is still limited and cannot meet the needs of commercial applications.
[0038] In order to solve these problems, the present invention proposes a new method for preparing lithium-rich manganese-based positive electrode materials. The implementation idea of this method is to form a nano-scale dynamic interface inside the material through cobalt and lithium, which can adjust the migration of cobalt and lithium ions under different electrochemical states, avoiding the passivation phenomenon after doping in the prior art; and introduce phosphorus-sulfur groups into the material system to interact with the lithium and cobalt elements in the material to form Li-PS4 and Co-PS4 complexes. The formation of these complexes can effectively stabilize the lattice structure of the material, inhibit the release of oxygen under high voltage, and improve the conductivity of the material by improving the efficiency of electron and ion transmission. At the same time, the dynamic interface design of the material and the reasonable sintering process can further enhance the structural stability and cycle life of the material.
[0039] Please refer to Figure 1 , which is a flow chart of a method for preparing a lithium-rich manganese-based positive electrode material in one embodiment of the present invention. The method for preparing a lithium-rich manganese-based positive electrode material specifically comprises the following steps:
[0040] S101: Mix and dissolve a manganese source, a cobalt source and a lithium source to prepare a metal salt solution.
[0041] The manganese source can be manganese nitrate or manganese acetate, the cobalt source can be cobalt nitrate or cobalt acetate, and the lithium source can be lithium nitrate or lithium acetate. These metal salts can be dissolved in water to form a uniform metal ion solution. By selecting a suitable solvent, such as deionized water, it is possible to ensure that the metal ions in the solution are stably dispersed to avoid premature precipitation or reaction.
[0042] In the metal salt solution, various metal ions are evenly dispersed, avoiding local enrichment or loss of material components, which is conducive to the precipitation and crystal growth of materials in subsequent steps. Especially in lithium-rich manganese-based materials, the distribution of manganese, cobalt and lithium will significantly affect the structural stability and electrochemical properties of the material.
[0043] In an exemplary embodiment, the molar ratio of manganese, cobalt and lithium in the metal salt solution is 1: (0.05-0.5): (1.1-1.3). Manganese is the core active element in the lithium-rich manganese-based positive electrode material, providing the basis for high specific capacity; cobalt is used to enhance the conductivity and structural stability of the material; and the excessive introduction of lithium is to ensure the specific capacity of the material and the sufficient supply of lithium during the use of the battery.
[0044] Manganese (Mn) is the main component of the positive electrode material and is a key element to provide high capacity. The theoretical capacity of lithium-rich manganese-based positive electrode materials is very high, partly due to the contribution of manganese. However, since manganese easily causes structural distortion and lattice oxygen release during battery cycling, resulting in rapid capacity decay, the manganese content in the material must be controlled within a reasonable range and structural stability needs to be maintained through appropriate doping with other elements.
[0045] The molar ratio range of cobalt (Co) is set to 0.05~0.5, with the aim of improving the conductivity and structural stability of the material by introducing a small amount of cobalt. Cobalt exhibits good conductivity in electrochemical reactions. At the same time, cobalt can stabilize the lattice in the crystal structure of the material, reduce the valence change of manganese during the cycle, and thus delay the occurrence of lattice distortion. When the cobalt content is too low (less than 0.05), it may not be enough to effectively improve the conductivity and stability of the material. If the content is too high (greater than 0.5), it may affect the specific capacity of the material, because the specific capacity of cobalt is low and the cost of cobalt is high, so excessive cobalt doping may not have a cost-effective advantage.
[0046] The molar ratio of lithium (Li) is set to 1.1~1.3 to compensate for the lithium loss of the material during the actual battery operation process. During the first charge and discharge process of lithium-rich manganese-based materials, due to the irreversible process of redox reaction inside the material, part of the lithium will be consumed and unable to participate in subsequent reactions. Therefore, an appropriate amount of excess lithium supplementation is required to ensure the high capacity retention rate of the battery after long-term use. The excessive introduction of lithium can not only effectively compensate for the loss of lithium in the material, but also improve the rate performance of the battery by enhancing lithium ion conductivity. For example, when the molar ratio of lithium is set to 1.2, the material can maintain a good lithium ion migration path in the electrochemical cycle while maintaining a high battery capacity.
[0047] S102: adding an organic phosphorus sulfide, a complexing agent and a dispersant to the metal salt solution, adjusting the pH of the system to 9-11, and reacting at 60-80° C. to obtain a precursor solution.
[0048] In conventional technology, it is generally believed that the introduction of P and S will increase the instability of lithium-rich manganese-based materials, easily cause phase change or structural inhomogeneity of the materials, and perform poorly under high rate conditions. In the present invention, organic phosphorus sulfides (such as triethyl thiophosphate, diethyl dithiophosphate, etc.) will decompose at high temperatures to release phosphorus sulfur groups (such as PS4 3- ), these groups can react with metal ions (such as lithium, cobalt, manganese) to form Li-PS4 and Co-PS4 complexes. These phosphorus-sulfur groups can not only improve the conductivity of the material, but also stabilize the lattice structure of the material and reduce the problem of oxygen release under high voltage. The dynamic interface regulation function of the phosphorus-sulfur group enables it to provide a good lithium ion migration channel during the electrochemical reaction, improving the rate performance and cycle life of the material.
[0049] The role of complexing agents is to stabilize metal ions in the solution and prevent them from precipitating prematurely, thereby ensuring that the metal ions in the solution are evenly distributed. Complexing agents include ethylenediaminetetraacetic acid (EDTA), triethanolamine (TEA), ammonia, etc. Complexing agents can form stable complexes with metal ions such as manganese, cobalt, and lithium through complexation, avoiding unnecessary precipitation during pH adjustment or heating reactions.
[0050] The role of the dispersant is to prevent the metal precursor particles from agglomerating during the reaction. Dispersants can be citric acid, polyethylene glycol (PEG) and polyvinyl pyrrolidone (PVP), which can form stable colloids in the solution to ensure uniform distribution of nanoparticles in the precursor solution, and can effectively prevent particles from agglomerating during the reaction, especially in the subsequent precipitation reaction and aging process. The particle size and uniformity of the precursor will affect the performance of the final material. By rationally selecting a dispersant, it can be ensured that the prepared precursor particles are evenly dispersed, thereby improving the performance of the final positive electrode material.
[0051] A pH value of 9 to 11 (alkaline conditions) is beneficial for controlling the existence state of metal ions in the reaction system, preventing the metal ions from precipitating prematurely during the reaction, and also promoting the complexation between organic phosphorus sulfides and metal ions.
[0052] If the pH is too low (<9), metal ions tend to combine with hydrogen ions in the solution to form unstable or other insoluble byproducts, resulting in premature precipitation, which affects the subsequent uniform reaction. In addition, the reactivity of the P=S bond will be affected and may not be able to fully combine with the metal ions, resulting in low efficiency of the introduction of phosphorus-sulfur groups.
[0053] If the pH is too high (>11), metal ions such as cobalt and manganese are prone to generate metal hydroxide precipitation, resulting in uneven distribution of cobalt and manganese in the material. It may also cause excessive hydrolysis of phosphosulfide, destroy the P=S bond, generate polysulfide or other insoluble compounds, and produce unwanted by-products in the reaction system, affecting the uniformity and subsequent performance of the material.
[0054] In an exemplary embodiment, the molar ratio of the organic phosphorus sulfide to the cobalt in the metal salt solution is (0.08-0.2): 1. The amount of the organic phosphorus sulfide is 8% to 20% of the cobalt source, that is, in the reaction system, the role of the organic phosphorus sulfide in the reaction is auxiliary, not used in large quantities, but introduced in appropriate amounts to provide phosphorus sulfur groups to cooperate with cobalt ions in subsequent reactions to form stable Li-PS4 and Co-PS4 complexes.
[0055] Specifically, the precursor solution contains cobalt-lithium heterogeneous nanoparticles, and the average particle size of the cobalt-lithium heterogeneous particles is 50-150 nm.
[0056] Cobalt-lithium heterogeneous nanoparticles contain two elements, cobalt and lithium, and they form nano-scale particles through heterogeneity. This heterogeneous structure helps to improve the conductivity and structural stability of lithium-rich manganese-based materials. Cobalt and lithium form nano-scale particles through heterogeneity, and this structure can form multiple dynamic heterogeneous interfaces in the material, thereby playing different functions during the charge and discharge process.
[0057] Specifically, the cobalt-lithium heterogeneous nanoparticles can make the cobalt-based phase and the lithium-based phase in the material evenly distributed through the synthesis process of the present invention, and form a dynamic interface at the nanoscale. Due to the complementarity of cobalt and lithium in electrochemical properties, these heterogeneous nanoparticles can simultaneously improve the electrochemical stability and conductivity of the material. The cobalt-based phase mainly plays a stabilizing role during the charging process. By forming a strong interface with the lithium-rich phase in the lithium-rich manganese-based material, the material's resistance to oxygen release is enhanced to prevent lattice distortion under high voltage. The lithium-based phase can quickly release lithium ions during discharge, forming an effective lithium ion conduction path, thereby improving the battery's rate performance.
[0058] The average particle size of cobalt-lithium heterogeneous particles is 50~150nm, which can ensure the efficient transmission of the conductive network inside the material. At the same time, it can increase the contact area with the electrolyte through the high specific surface area of the nanoparticles and enhance the rate of the electrochemical reaction.
[0059] During the charge and discharge process of the material, the cobalt-lithium heterogeneous nanoparticles can continuously adjust their internal ion transmission paths through the action of the dynamic interface, ensuring that the material maintains efficient charge and ion conductivity during long-term use. For example, the lithium-based phase can quickly release lithium ions in the low-voltage area, while the cobalt-based phase provides structural support in the high-voltage area to avoid material performance degradation caused by oxygen release. The uniform distribution of these cobalt-lithium heterogeneous nanoparticles can effectively improve the overall conductivity of the positive electrode material, allowing lithium ions to migrate at a higher rate in the positive electrode material, meeting the needs of rapid charge and discharge, while ensuring that the positive electrode material can still maintain a high structural integrity under high voltage conditions.
[0060] S103: adding lithium hydroxide solution to the precursor solution to perform a precipitation reaction, and aging the precipitate at 50-80° C. for 4-8 hours.
[0061] The main purpose of adding lithium hydroxide solution is to provide sufficient lithium source for the material and ensure that lithium is evenly distributed in the structure of the material. Lithium is a core element in lithium-rich manganese-based positive electrode materials and participates in the electrochemical reaction of the battery. The addition of lithium hydroxide not only provides lithium ions, but also promotes other metal ions (such as manganese and cobalt) in the solution to react with lithium hydroxide to form hydroxide precipitates. This precipitation reaction is a key step to ensure that the metal ions (manganese, cobalt, lithium) are fully combined and evenly distributed.
[0062] The precipitation reaction process can not only form a precipitate rich in manganese and lithium, but also control the precursor particle size and morphology of the material. For example, when manganese and cobalt ions react with lithium hydroxide, manganese and cobalt hydroxides are generated, and these hydroxides are further converted into oxides or composite materials during the subsequent sintering process. Through the precipitation reaction, the ratio of lithium, cobalt, and manganese in the material can be ensured to be accurate and evenly distributed, which contributes to the structure and electrochemical properties of the final material. During the reaction, the particle size and morphology of the precipitate can be adjusted by controlling the addition rate of lithium hydroxide and the reaction temperature to ensure the uniformity of the material and the controllability of the reaction. For example, the problem of uneven particles caused by the rapid generation of precipitates can be avoided by slowly dripping lithium hydroxide solution.
[0063] After the precipitate is generated, it needs to be aged for 4 to 8 hours at a temperature of 50 to 80°C. Aging refers to maintaining the state of the precipitate at a certain temperature and time to promote the crystallization and structural optimization of the precursor particles. During the aging process, the microstructure of the precipitate will undergo further changes, the crystallinity of the particles will increase, and the morphology of the particles will tend to be stable. In the range of 50 to 80°C, the higher the aging temperature, the faster the reaction rate and the better the crystallization of the particles, but if the temperature is too high, it may cause agglomeration between the particles. The aging time also needs to be controlled. If the time is too short, the crystallization is insufficient, affecting the subsequent material performance; if the time is too long, it may cause excessive growth of particles, affecting the uniformity and specific surface area of the material.
[0064] In an exemplary embodiment, the molar ratio of manganese in the precursor solution to lithium in the lithium hydroxide solution is 1: (1-1.2). Manganese, as the main active ingredient in the positive electrode material, provides the material's specific capacity; while lithium serves as the core ion of the electrochemical reaction, participating in the insertion and extraction of lithium ions during the charge and discharge process.
[0065] Introducing enough lithium into the material is also to balance the ratio of manganese to lithium in the material and ensure the stability of the material during the charge and discharge cycle. The valence state of manganese may change during the electrochemical process, especially under high voltage conditions, which can easily lead to the destruction of the material lattice. The excessive introduction of lithium can not only play a role in charge compensation in the electrochemical process, but also stabilize the lattice structure of the material and prevent lattice collapse or distortion.
[0066] S104: The aged precipitate is heated at 150-200° C. for 30-60 min, and then washed and dried.
[0067] The main purpose of step S104 is to perform low-temperature solidification treatment on the precipitate to reduce the dissolution or loss of the precipitate in the subsequent washing process. This step partially solidifies the precipitate by low-temperature heating, and promotes some organic phosphorus sulfides in the precipitate to react with metal ions to form stable intermediate compounds, thereby avoiding the loss of organic phosphorus sulfide precursors in the washing process.
[0068] Organic phosphorus-sulfur compounds have a certain solubility in the solution. Direct washing will cause some organic phosphorus-sulfides to be washed away, affecting the performance of the material. By heating at a low temperature of 150~200℃, some organic components in the organic phosphorus-sulfides will decompose and react initially with metal ions such as lithium and cobalt to form insoluble intermediate substances. In actual operation, the aged precipitate can be placed in an oven at 180℃ and heated for 45 minutes. Such treatment can ensure sufficient reaction and avoid lattice changes or excessive agglomeration of particles that may be caused by excessive temperature.
[0069] The purpose of washing after heating is to remove residual reactants, solvents, and unreacted by-products in the material. In actual operation, the washing solvent can be deionized water or anhydrous ethanol, which is selected according to the solubility characteristics of the precipitate. For example, the use of anhydrous ethanol can effectively remove residual organic matter while preventing water from dissolving the material again. During washing, multiple washing and filtering are required to ensure that the residual impurities are removed.
[0070] S105: The dried precipitate is mixed with a lithium source and sintered in stages at a sintering temperature of 200 to 850° C. for a sintering time of 10 to 20 hours to obtain a lithium-rich manganese-based positive electrode material.
[0071] The main purpose of mixing the dried precipitate with a lithium source is to supplement the lithium content and ensure that the lithium concentration reaches an appropriate ratio during the sintering process. This is because during the high-temperature sintering process, the lithium element is easily volatilized, resulting in insufficient lithium content in the final material. The choice of lithium source is usually lithium hydroxide (LiOH) or lithium carbonate (Li2CO3), which will decompose at high temperatures, releasing lithium ions and forming stable lithium-rich manganese-based positive electrode materials with other metal elements in the material (such as manganese, cobalt, etc.).
[0072] The purpose of staged sintering is to gradually control the crystallization process of the material, which can effectively inhibit the agglomeration of particles, make the grains in the material evenly distributed, and enable the microstructure of the material to be gradually formed and stabilized. In the present invention, staged sintering is usually divided into three stages: pre-sintering, medium-temperature sintering and high-temperature sintering:
[0073] Pre-burning (200~300℃): This stage is mainly to remove residual organic matter and moisture in the material. Although most of the moisture and volatile substances have been removed in the previous drying process, the pre-burning process at 200~300℃ can further remove the residual organic matter in the precursor to prevent them from having adverse reactions during high-temperature sintering. For example, pre-burning at 250℃ for 4 hours can ensure that all organic matter is completely decomposed and the precursor structure begins to crystallize initially.
[0074] Medium-temperature sintering (500~600℃): The medium-temperature sintering stage is the initial crystallization stage of the material. In the temperature range of 500~600℃, metal ions such as manganese and cobalt react with lithium ions to form a preliminary crystal structure. The temperature selection at this stage needs to be reasonably controlled. Too low a temperature will lead to insufficient crystallization, while too high a temperature may cause particle agglomeration. Through medium-temperature sintering, the grains of the material can gradually grow and begin to form the layered structure required for lithium-rich manganese-based positive electrode materials. For example, sintering at 600℃ for 6 hours can ensure that the internal lattice of the material is gradually improved, laying the foundation for subsequent high-temperature sintering.
[0075] High temperature sintering (700~850℃): This stage is the final forming stage of the material. At a high temperature of 700~850℃, the crystal structure of the material will be further optimized, and the interface between the particles will be further enhanced. At this time, lithium ions and metal ions are completely embedded in the lattice structure of the material to form a stable lithium-rich manganese-based positive electrode material. At high temperatures, the conductivity and electrochemical properties of the material will be significantly improved. The high temperature sintering time is controlled at 10~20 hours. This time range can ensure that the crystal structure of the material is fully formed, while avoiding excessive sintering of the material, grain growth or abnormal sintering due to too long a time. For example, after sintering at 850℃ for 10 hours, the material can form a stable lattice with good conductivity and structural stability.
[0076] Specifically, the lithium-rich manganese-based positive electrode material contains Li-PS4 and Co-PS4 complexes, and the Li-PS4 and Co-PS4 complexes are located on the grain surfaces and grain boundary regions of the lithium-rich manganese-based positive electrode material.
[0077] Li-PS4 and Co-PS4 complexes are phosphorus-sulfur groups (PS4 3- ) combined with lithium and cobalt ions to form complex compounds. During high-temperature sintering, organic phosphorus sulfides such as triethyl trithiophosphate or diethyl phosphorothioate release PS4 when decomposed. 3- groups, which interact with lithium ions (Li + ) and cobalt ions (Co 2+) to form Li-PS4 and Co-PS4 complexes. These complexes are distributed on the surface and grain boundary regions of the material, and can build dynamic interfaces inside the material, providing stable electron and ion transmission channels.
[0078] The Li-PS4 complex is mainly located on the surface of the material's grains. The grain surface is an important area where electrochemical reactions occur, and the insertion and extraction of lithium ions usually occur at this interface. The Li-PS4 complex stabilizes the structure of the grain surface, reduces lattice distortion and oxygen release problems, and ensures that lithium ions can be smoothly inserted and extracted. The Li-PS4 complex can improve the lithium ion conductivity of the material and enhance the charge and discharge performance of the material under high rate conditions. For example, Li-PS4 can provide a more stable transmission path for lithium ions through chemical bonding with lithium ions, thereby improving the material's rate performance and charging efficiency.
[0079] The Co-PS4 complex is mainly distributed in the grain boundary area of the material. The grain boundary area is the contact surface between the particles. During the charge and discharge process, these areas are prone to stress concentration, leading to structural damage and capacity attenuation. The presence of the Co-PS4 complex can form a stable chemical barrier at the grain boundary to prevent excessive accumulation of interfacial stress between the particles, thereby delaying the structural degradation of the material during the cycle. In addition, the Co-PS4 complex can also enhance the overall conductive network of the material by improving electronic conductivity, ensuring smoother transfer of charge between grains. For example, during the charge and discharge cycle of the material, the Co-PS4 complex can effectively reduce the resistance at the grain boundary and improve the overall conductivity, thereby reducing the internal resistance loss of the material and increasing the output power of the battery.
[0080] The role of these complexes is not limited to improving conductivity and structural stability. They can also slow down the attenuation of materials in long-term cycles by dynamically adjusting the surface and interface chemical environment of the material. Specifically, during the charge and discharge process, Li-PS4 and Co-PS4 complexes can form reversible chemical adjustments on the surface and grain boundaries of the material as lithium ions are embedded and extracted, preventing irreversible chemical reactions or stress accumulation on the surface and interface of the material. This dynamic adjustment mechanism can extend the cycle life of the material, allowing the battery to maintain a high capacity retention rate after long-term use.
[0081] Specifically, the grain surface and grain boundary region of the lithium-rich manganese-based positive electrode material form a cobalt-oxygen cluster nanostructure. The cobalt-oxygen cluster (Co-O clusters) nanostructure is composed of cobalt ions (Co 2+ / Co 3+ ) and oxygen ions (O 2- ) Nanoscale structures formed by dynamic bonding on the surface of a material or at grain boundaries.
[0082] Through the aforementioned staged sintering process, the reaction between cobalt ions and oxygen ions can be gradually controlled to form a stable cobalt-oxygen cluster nanostructure. The initial generation of cobalt-oxygen clusters is achieved at 600°C, and then the formation of the crystal structure is further optimized at 850°C, making it stable and distributed in the grain boundaries and surface areas of the material.
[0083] As a transition metal, cobalt has various oxidation states, mainly Co 2+ and Co 3+ In electrochemical reactions, cobalt ions can undergo reversible redox reactions between these two oxidation states, and cobalt-oxygen clusters can regulate the charge balance and stress state in the material through the redox reactions of cobalt ions during the charge and discharge process.
[0084] During the charge and discharge cycle, the material's lattice will generate stress and microcracks due to the repeated insertion and extraction of lithium ions. These cracks gradually expand at the grain boundaries and surfaces, causing structural degradation of the material. The cobalt ions in the cobalt-oxygen cluster can release electrons in cracks or stress concentration areas through redox reactions or change oxidation states through ion migration to relieve local stress concentration. This dynamic regulation mechanism prevents cracks from expanding rapidly, thereby playing a role in crack repair and stress relief.
[0085] For example, when cracks form at grain boundaries or surfaces, Co 2+ It will form a strong cobalt-oxygen bond by combining with oxygen and oxidize to Co 3+ , resulting in changes in chemical bond energy, thereby inhibiting further crack expansion and even filling these microcracks.
[0086] The redox reaction of cobalt-oxygen clusters can not only maintain the stability of the material structure, but also improve the charge and discharge efficiency of the battery by increasing the electronic conductivity of the material in the electrochemical reaction. 2+ Can be oxidized to Co 3+ , providing more electron conduction channels, thereby improving the conductivity of the material and reducing the resistance to electron transmission. The dynamic redox reaction can also adjust the charge distribution inside the material and maintain the electrochemical stability of the material under high-rate charge and discharge conditions.
[0087] In addition, the nanostructure of cobalt-oxygen clusters has a high specific surface area, which enables them to form an effective conduction network and chemical reaction active area in the microstructure of the material. Nanoscale cobalt-oxygen clusters can be evenly distributed on the grain surface and grain boundary area of the material, forming a large number of conduction channels and improving the migration efficiency of electrons and lithium ions.
[0088] In one embodiment of the present invention, a lithium-rich manganese-based positive electrode material is further provided. The lithium-rich manganese-based positive electrode material is prepared by the above-mentioned preparation method.
[0089] In one embodiment of the present invention, a lithium-ion battery is provided. The lithium-ion battery includes the aforementioned lithium-rich manganese-based positive electrode material.
[0090] The present invention will be further described below in conjunction with specific embodiments. Example 1
[0091] (1) Preparation of metal salt solution
[0092] A metal salt solution was prepared according to the following proportions: 0.2 mol of manganese nitrate (Mn(NO3)2), 0.08 mol of cobalt nitrate (Co(NO3)2) and 0.25 mol of lithium nitrate (LiNO3) were dissolved in deionized water to prepare a uniform metal salt solution.
[0093] (2) Preparation of precursor solution
[0094] 0.01 mol of triethyl thiophosphate was added to the metal salt solution as an organic phosphorus sulfide, followed by 0.05 mol of ethylenediaminetetraacetic acid (EDTA) as a complexing agent, and finally 0.05 mol of polyethylene glycol (PEG) as a dispersant. The pH value was adjusted to 10.3 by gradually adding ammonia water, and reacted at 80° C. for 2 hours to form a uniform precursor solution.
[0095] (3) Precipitation reaction and aging
[0096] 200 mL of 1 mol / L lithium hydroxide solution was slowly added to the precursor solution to perform a precipitation reaction. After the precipitation reaction was completed, the precipitate was kept at 65° C. for 6 hours to make the morphology of the cobalt-lithium heterogeneous particles more uniform and improve the crystallinity.
[0097] (4) Preliminary heat treatment
[0098] After aging, the precipitate was heated to 180°C for 40 minutes. The heating treatment at this stage was used to initially solidify the precipitate to ensure that it would dissolve less during the subsequent washing process. The material was then washed several times with deionized water to remove residual reactants, unreacted solutes and organic compounds. After washing, the material was placed in an oven at 100°C for 2 hours.
[0099] (5) Sintering
[0100] The dried precipitate is fully mixed with lithium carbonate (Li2CO3, 0.06 mol) to form a uniform sintered precursor, and then pre-fired at 250°C for 4 hours to remove residual organic matter and moisture; then the temperature is raised to 600°C and kept for 4.5 hours to promote the initial crystallization reaction of the material; finally, the temperature is raised to 850°C and kept for 10 hours. This high-temperature sintering stage can form the lattice structure of the lithium-rich manganese-based positive electrode material.
[0101] (6) Cooling and collection
[0102] After sintering, the material was naturally cooled to room temperature to obtain a lithium-rich manganese-based positive electrode material. Electron microscopy showed that the obtained material had a uniform particle distribution, with Li-PS4, Co-PS4 complexes and cobalt-oxygen cluster nanostructures evenly distributed on the surface and grain boundaries. Figure 2 is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1, Figure 2 It can be seen that a rich and uniform nanostructure is formed on the surface of the material. Example 2
[0103] The difference compared with Example 1 is that the pH value of the precursor solution in this embodiment is adjusted to 9 during the preparation process, and the other preparation methods and conditions are consistent with those in Example 1. Example 3
[0104] The difference compared with Example 1 is that the pH value of the precursor solution in this embodiment is adjusted to 11 during the preparation process, and the other preparation methods and conditions are consistent with those in Example 1. Example 4
[0105] The difference compared with Example 1 is that in this example, diethyl dithiophosphate is used as the organic phosphorus sulfide, and the rest of the preparation methods and conditions are consistent with those in Example 1. Figure 3 is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 4. Figure 3 It can be seen that a rich and uniform nanostructure is formed on the surface of the material. Example 5
[0106] The difference compared with Example 1 is that the aging time in this example is 4 hours, and the other preparation methods and conditions are consistent with those in Example 1. Example 6
[0107] The difference compared with Example 1 is that the aging time in this example is 8 hours, and the other preparation methods and conditions are consistent with those in Example 1.
[0108] Comparative Example 1
[0109] The difference compared with Example 1 is that the pH value of the precursor solution in this comparative example is adjusted to 8.5 during the preparation process, and the rest of the preparation method and conditions are consistent with Example 1. Figure 4 is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1. Figure 4 It can be seen that there are fewer nanostructures formed on the surface of the material and the nanostructures are unevenly distributed.
[0110] Comparative Example 2
[0111] The difference compared with Example 1 is that the pH value of the precursor solution in this comparative example is adjusted to 11.5 during the preparation process, and the other preparation methods and conditions are consistent with those in Example 1. Figure 5 is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 2. Figure 5 It can be seen that there are fewer nanostructures formed on the surface of the material and the nanostructures are unevenly distributed.
[0112] Comparative Example 3
[0113] The difference compared with Example 1 is that the aging time in this comparative example is 3 hours, and the other preparation methods and conditions are consistent with those in Example 1. Figure 6 is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 3, Figure 6 It can be seen that the nanostructure formed on the surface of the material is not fully grown.
[0114] Comparative Example 4
[0115] The difference compared with Example 1 is that the aging time in this comparative example is 9 hours, and the other preparation methods and conditions are consistent with those in Example 1.
[0116] Comparative Example 5
[0117] The difference compared with Example 1 is that in this comparative example, the aged precipitate is not subjected to preliminary heat treatment, but is directly washed and dried. The rest of the preparation methods and conditions are consistent with those in Example 1. Figure 7 is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 5, Figure 7 It can be seen that fewer nanostructures are formed on the surface of the material.
[0118] Comparative Example 6
[0119] The difference compared with Example 1 is that in this comparative example, no organic phosphorus sulfide is added during the preparation of the precursor solution, and the rest of the preparation methods and conditions are consistent with those of Example 1. Figure 8 is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 6, Figure 8It can be seen that fewer nanostructures are formed on the surface of the material.
[0120] Comparative Example 7
[0121] The difference compared with Example 1 is that in this comparative example, no staged sintering is performed, but sintering is performed directly at 850° C. for 16 hours. The rest of the preparation method and conditions are consistent with those in Example 1. Fig. 9 is a scanning electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 7. Fig. 9 It can be seen that the material particles are seriously agglomerated.
[0122] Performance Testing
[0123] The positive electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 7 were mixed with a conductive agent (carbon black) and a binder (polyvinylidene fluoride) in a ratio of 90:5:5 to prepare a positive electrode slurry, which was then coated on an aluminum foil to prepare a positive electrode sheet. After drying, the positive electrode slurry was assembled with a metal lithium negative electrode sheet, a polypropylene microporous membrane separator and an electrolyte in a glove box to form a standard 2032 type button battery. After the battery was assembled and aged for 12 hours, its charge and discharge performance was tested.
[0124] Rate test: charging upper limit voltage 4.8V, discharging lower limit voltage 2.0V; 0.1C charge and discharge for 5 cycles; 1C charge and discharge for 5 cycles; 3C charge and discharge for 5 cycles; 5C charge and discharge for 5 cycles.
[0125] Cycle stability test: charging upper limit voltage 4.8V, discharging lower limit voltage 2.0V, 0.1C charge and discharge for 1 cycle for activation, 3C charge and discharge for 100 cycles; the test room temperature is constant at 25℃.
[0126] Internal resistance test: Use a multimeter to connect the positive and negative poles of the battery for testing.
[0127] The test results are shown in Table 1:
[0128] Table 1 - Performance test results
[0129]
[0130] In summary, the lithium-rich manganese-based positive electrode material and its preparation method, and the lithium-ion battery provided by the present invention can adjust the migration of cobalt and lithium ions under different electrochemical states by forming a nanoscale dynamic interface between cobalt and lithium inside the material, thereby avoiding the passivation phenomenon after doping in the prior art; and introduce phosphorus-sulfur groups into the material system to interact with the lithium and cobalt elements in the material to form Li-PS4 and Co-PS4 complexes, which can effectively stabilize the lattice structure of the material and improve the conductivity of the material by improving the efficiency of electron and ion transmission.
[0131] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0132] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: S101: Mix and dissolve a manganese source, a cobalt source and a lithium source to prepare a metal salt solution; S102: adding an organic phosphorus sulfide, a complexing agent and a dispersant to the metal salt solution, adjusting the pH of the system to 9-11, and reacting at 60-80° C. to obtain a precursor solution; S103: adding a lithium hydroxide solution to the precursor solution to perform a precipitation reaction, and aging the precipitate at 50-80° C. for 4-8 hours; S104: heating the aged precipitate at 150-200° C. for 30-60 min, washing, and drying; S105: mixing the dried precipitate with a lithium source, and performing segmented sintering at a sintering temperature of 200 to 850° C. for a sintering time of 10 to 20 hours to obtain a lithium-rich manganese-based positive electrode material; The staged sintering includes: pre-sintering at 200-300°C, medium-temperature sintering at 500-600°C, and high-temperature sintering at 700-850°C.
2. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The molar ratio of manganese, cobalt and lithium in the metal salt solution in step S101 is 1: (0.05-0.5): (1.1-1.3).
3. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The organic phosphorus sulfide comprises at least one of triethyl thiophosphate and diethyl dithiophosphate; and / or The complexing agent includes at least one of ethylenediaminetetraacetic acid, triethanolamine and ammonia water; and / or The dispersant includes at least one of citric acid, polyethylene glycol and polyvinyl pyrrolidone.
4. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The precursor solution in step S102 contains cobalt-lithium heterogeneous nanoparticles, and the average particle size of the cobalt-lithium heterogeneous particles is 50-150 nm.
5. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The molar ratio of the organic phosphorus sulfide to the cobalt in the metal salt solution in step S102 is (0.08-0.2): 1; and / or In step S103, the molar ratio of manganese in the precursor solution to lithium in the lithium hydroxide solution is 1: (1-1.2).
6. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The segmented sintering method in step S105 includes: Pre-sinter at 250℃ for 2~4h; then keep at 600℃ for 4~6h; finally sinter at 850℃ for 10h.
7. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The lithium-rich manganese-based positive electrode material contains Li-PS4 and Co-PS4 complexes, and the Li-PS4 and Co-PS4 complexes are located on the grain surface and grain boundary area of the lithium-rich manganese-based positive electrode material.
8. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: A cobalt-oxygen cluster nanostructure is formed on the grain surface and grain boundary region of the lithium-rich manganese-based positive electrode material.
9. A lithium-rich manganese-based positive electrode material, characterized in that: The lithium-rich manganese-based positive electrode material is prepared by any preparation method according to claims 1 to 8.
10. A lithium ion battery, characterized in that: Comprising the lithium-rich manganese-based positive electrode material as described in claim 9.
Citation Information
Patent Citations
Sulfide solid electrolyte stable to lithium, preparation method thereof and solid-state battery with solid electrolyte
CN110911733A
Negative electrode material and preparation method thereof, negative electrode plate and all-solid-state battery
CN118398778A
Cited By
High-entropy cobalt-free lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN120483279A
High-entropy cobalt-free lithium-rich manganese-based positive electrode material, preparation method and application thereof
CN120483279B